Evaluation of Parasiticide Treatment with Benznidazol in the Electrocardiographic, Clinical, and Serological Evolution of Chagas Disease. - Abilio Augusto Fragata-Filho; Francisco Faustino França; Claudia da Silva Fragata; Angela Maria Lourenço; Cristiane Castro Faccini; Cristiane Aparecida de Jesus Costa (Public Library of Science (PLoS), 2016)
INTRODUCTION:Chagas disease is one of the most important endemic parasitic diseases in Latin America. In its chronic phase, progression to cardiomyopathy has high morbidity and mortality. The persistence of a normal electrocardiogram (ECG) provides a similar prognosis to that of a non-diseased population. Benznidazole (BNZ) is the only drug with trypanocidal action available in Brazil. MATERIALS/METHODS/RESULTS:A group of 310 patients with chronic Chagas disease who had normal ECGs at the first medical visit performed before 2002 were included. There were 263 patients treated with BNZ and 47 untreated. The follow-up period was 19.59 years. Univariate analyses showed that those treated were younger and predominantly male. As many as 79.08% of those treated and 46.81% of those untreated continued with normal electrocardiograms (p <0.0001). The occurrence of electrocardiographic abnormalities and relevant clinical events (heart failure, stroke, total mortality, and cardiovascular death) was less prevalent in treated patients (p <0.001, p: 0.022, p: 0.047 respectively). In multivariate analyses, the parasiticide treatment was an independent variable for persistence of a normal ECG pattern, which was an independent variable in the prevention of significant clinical events. The immunofluorescence titers decreased with the parasitological treatment. However, the small number of tests in untreated patients did not allow the correlation of the decrease of these titers with electrocardiographic alterations. CONCLUSION:These data suggest that treatment with benznidazole prevents the occurrence of electrocardiographic alterations. On the other hand, patients who develop ECG abnormalities present with more significant clinical events.